2023
DOI: 10.1164/rccm.202110-2414oc
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Fibroblast Activation Protein Expression in Interstitial Lung Diseases

Abstract: Rationale Sustained activation of lung fibroblasts and the resulting oversynthesis of the extracellular matrix are detrimental events for patients with interstitial lung diseases (ILDs). Lung biopsy is a primary evaluation technique for the fibrotic status of ILDs, and is also a major risk factor for triggering acute deterioration. Fibroblast activation protein (FAP) is a long-known surface biomarker of activated fibroblasts, but its expression pattern and diagnostic implications in ILDs are poorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 46 publications
4
34
0
Order By: Relevance
“…Thus, even though at day 21 fibroblasts were still activated in BLM + ICG mice, as revealed by FAP-1α quantification, the levels of Collagen I were not significantly increased. Importantly, we showed that in vivo detection of FAP-1α can assess the fibrotic activity of BLM + ICG-mediated injury, as was recently reported for the BLM model ( 41 ). Because of the close temporal association between the development of high-grade fibrosis and the appearance of emphysema-like features, we hypothesize that mechanical traction on lung parenchyma, exerted by the accumulated fibrotic tissue, might be responsible for (or at least contribute to) the observed airspace enlargements and increase of hyperinflated areas.…”
Section: Discussionsupporting
confidence: 80%
“…Thus, even though at day 21 fibroblasts were still activated in BLM + ICG mice, as revealed by FAP-1α quantification, the levels of Collagen I were not significantly increased. Importantly, we showed that in vivo detection of FAP-1α can assess the fibrotic activity of BLM + ICG-mediated injury, as was recently reported for the BLM model ( 41 ). Because of the close temporal association between the development of high-grade fibrosis and the appearance of emphysema-like features, we hypothesize that mechanical traction on lung parenchyma, exerted by the accumulated fibrotic tissue, might be responsible for (or at least contribute to) the observed airspace enlargements and increase of hyperinflated areas.…”
Section: Discussionsupporting
confidence: 80%
“…68 Ga-FAPI-04 PET/computed tomography has been performed in systemic sclerosis–associated ILD, and the degree of probe uptake was associated with disease progression ( 14 ). This study by Yang and colleagues ( 1 ) illustrates several important applications of molecular imaging to ILD. First, it can be used to obtain molecular information otherwise not available and thus advance our understanding of molecular heterogeneity within individuals and ILD subtypes.…”
mentioning
confidence: 88%
“…In this issue of the Journal , Yang and colleagues (pp. 160–172 ) evaluate “fibroblast activating protein” (FAP) as a molecular marker of disease activity with the potential to be leveraged for prognostic purposes ( 1 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…FAPI PET/CT correlated well with endoscopic, computed tomography enterography, and disease biomarkers. It was highly sensitive in the detection of different classes of lesions in all intestinal segments Treutlein et al [ 8 ] 2023 Germany Systemic sclerosis 14 [ 68 Ga]Ga-FAPI PET/CT may be a diagnostic option to monitor cardiac fibroblast activity being able to visualize myocardial fibrosis related to systemic sclerosis Yang et al [ 9 ] 2023 China Interstitial lung diseases 83 [ 68 Ga]Ga-FAPI PET/CT can assess the profibrotic activity of interstitial lung diseases. Radiolabelled FAPI uptake was significantly related to lung function decline in patients with interstitial lung diseases Röhrich et al [ 10 ] 2022 Germany Interstitial lung diseases 15 [ 68 Ga]Ga-FAPI PET/CT is a promising method for detecting fibrotic interstitial lung diseases and associated lung cancer Wang et al [ 11 ] 2022 China Light-chain amyloidosis 30 [ 68 Ga]Ga-FAPI PET/CT is feasible in detecting myocardial fibroblast activation in patients with light-chain cardiac amyloidosis in correlation with myocardial remodeling.…”
mentioning
confidence: 99%